Earth systems today David King ... et al.]. - King, David; Thomson Learning (Firm).; Living Text (Firm). (Pacific Grove, Calif. Brooks/Cole, 2001)
A tool for courses or labs that cover earth-science topics, including physical geology, historical geology, earth science, earth-systems science, oceanography, environmental science, or meteorology.
CD-ROM.
Made with Macromedia.
"Direct Internet interaction" - container.
Title from title screen.
System requirements: IBM compatible PC; Pentium I or later, 266MHz or later, 64MB RAM, 50MB disk space, Windows 95/98/NT4.
System requirements: Macintosh; PowerMac, IMac, G3, G4 and later, 200MHz or later, 80MB RAM, 50MB disk space, OS 8.6 and later.
Keywords: Earth sciences -- Computer-assisted instruction; Physical geology; Historical geology; Oceanography; Environmental science; Meteorology